BATANG NIBUNG'S NATURAL DURABILITY (Oncosperma tigillarium) AGAINST ATTACKS SOIL TERMITES (Coptotermes curvignathus) - Akmal Gian Fernando; Rudianda Sulaeman; Viny Volcherina Darlis (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2020)
Nibung (Oncosperma tigillarium) is a palm-like plant that grows in Southeast Asia and covers almost all parts of Indonesia. Nibung stem is very resistant to use in coastal areas by the community as building material and as a support pole. This study aims to determine the durable class of Batang Nibung (Oncosperma Tigillarium) from termite attack (Coptotermes curvignathus). This research method uses a Complete Random Design (CRD) balanced nest design. Nibung's Natural Endurance Test on Soil Termites (Coptotermes curvignathus) using SNI 01-7207-2006. Nibung stem as a whole has a decrease in average Weight Loss (WL) value of 15.37% and is included in the class IV durable, while the nibung stem which has the smallest WL is found at the base of the skin (Pk) which is 2.39% classified in the durable class I and the part that has the most WL is found on the tip of the skin (Uk), which is 24.09% belonging to the durable V class.